Missed Opportunities for Early Diabetes Screening in Pregnancy - Battarbee, Ashley N.; Cavallini, Maximiliano; Keller, Catherine; Boggess, Kim A. (American Journal of Perinatology, 2019)
Objective This study aimed to identify characteristics of women at risk of undiagnosed type 2 diabetes mellitus (T2DM) that fail to receive early pregnancy screening.Study Design This was a retrospective case–control study of at-risk women who initiated care at the University of North Carolina at Chapel Hill at <21 weeks from January 2015 to December 2015. In 2013, the American College of Obstetricians and Gynecologists and the American Diabetes Association recommended women with prior GDM, glucose intolerance, or body mass index (BMI) ≥ 30 kg/m2 receive early pregnancy screening for undiagnosed T2DM. We defined early screening as 1-hour 50-g glucose challenge test or hemoglobin A1c at <21 weeks' gestation. Cases were women who did not have early screening, and controls were women who did. Modified Poisson regression with robust error variance estimated relative risks of factors associated with missed early screening.Results Of the 1,932 women who initiated care at <21 weeks, 257 (13%) women were at risk of undiagnosed T2DM and, thus, candidates for early screening. However, 129 (50.2%) women were not screened. Higher BMI and prior GDM were associated with a lower relative risk of missed screening.Conclusion Higher BMI and prior GDM increased the likelihood of early diabetes screening, but only half of at-risk women were screened. Provider education and best practice alert systems are needed to increase screening for undiagnosed T2DM.
Keywords: screening; diabetes; early; pregnancy; obesity